Ultra-Processed Foods Consumption and Lipid Profile in Brazilian Children. (29th May 2020) - Hoffman, Daniel; Leffa, Paula dos; Sangalli, Caroline; Valmórbida, Julia; Rauber, Fernanda; Vitolo, Márcia
Abstract: Objectives: The consumption of ultra-processed foods (UPF) plays a role in the development of chronic diseases, but there is a limited number of studies targeting the association of its intake and risk of diseases in childhood. Our objective was to determine longitudinal trends of UPF intake and their impact on blood lipids in young children. Methods: A longitudinal cohort study of children at 3 and 6 years of age from low-income families in southern Brazil was conducted. Dietary data were collected through two 24-h recalls and UPF consumption was assessed by NOVA, a classification of foods based on the degree and purpose of industrial food processing. At 6 years of age, blood tests were performed to measure total cholesterol, LDL-cholesterol, HDL-cholesterol, and triglycerides. Multivariable linear regression analyses were used to assess differences across tertiles of UPF consumption at age 3 years on lipid profile at age 6 years. Results: Complete data were available for 308 children; of which, 52.0% were male. Regarding nutritional status, 18.0% of children at age 3 years and 18.4% at age 6 years were overweight. UPF represented a mean of 43% and 47% of the total energy intake at 3 and 6 years of age, respectively. The overall dietary contribution of UPF increased by 10% across three years of assessment. Higher UPF intake at age 3 years was associated with increased levels of total cholesterol (tertile 3 vs. tertile 1; β 8.51 mg/dL [95% CI 1.65 to 15.37]) and triglycerides (tertile 3 vs. tertile 1; β 9.69 mg/dL [(95% CI 0.97 to 18.42]) later at age 6 years. Conclusions: An increase in UPF consumption was associated with poor lipid profile at age 6 years. The results of our study emphasize the need for innovative strategies to reduce the consumption of ultra-processed foods, especially in early ages, to ensure lifelong health. Funding Sources: Brazilian Ministry of Health, Research Support Foundation of the State of Rio Grande do Sul (FAPERGS), Brazilian National Council for Scientific and Technological Development (CNPq) and Coordination for the Improvement of Higher Education Personnel (CAPES).